1949
DOI: 10.3733/hilg.v19n03p057
|View full text |Cite
|
Sign up to set email alerts
|

A lysimeter investigation of nitrogen gains and losses under various systems of covercropping and fertilization, and a discussion of error sources

Abstract: There is an enormous amount of literature concerning various phases of the nitrogen problem. Most of the work reported, however, has been carried out under cropping, management, fertilization, soil, and climatic conditions foreign to those common to this region, and hence has little or no local value. Only such work, therefore, as shows the general trend of findings elsewhere is reviewed here.Relative to unaccounted-for losses of nitrogen, there is evidence that under some conditions considerable nitrogen esca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1954
1954
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…The need for additional soil nitrogen to increase grass production has been indicated by responses to nitrogen fertilizer on all sites at the Experimental Range. This nitrogen deficiency is typical of foothill soils and has been reported on other areas (Dickey, et al, 1948;Chapman, et al, 1949). Response to added nitrogen has been impressive and consistent on some fairly deep, heavy soils and a program of nitrogen fertilization has been recommended for some foothill areas (Hoglund, et al, 1952).…”
Section: Second Response Is In Grassessupporting
confidence: 62%
“…The need for additional soil nitrogen to increase grass production has been indicated by responses to nitrogen fertilizer on all sites at the Experimental Range. This nitrogen deficiency is typical of foothill soils and has been reported on other areas (Dickey, et al, 1948;Chapman, et al, 1949). Response to added nitrogen has been impressive and consistent on some fairly deep, heavy soils and a program of nitrogen fertilization has been recommended for some foothill areas (Hoglund, et al, 1952).…”
Section: Second Response Is In Grassessupporting
confidence: 62%
“…Modem ecosys- Ecology,Vol. 74,No.2 tern experiments and comparisons have repeatedly noted a rapid accumulation of N in a variety of ecosystems containing symbiotic N 2 fixers (e.g., Chapman et al 1949, Tarrant and Miller 1963, Van Cleve et al 1971, Cromack et al 1979. At the same time, rapid N 2 fixation in symbiotic N 2 fixers is suggested by direct measures of nitrogenase activity extrapolated to an area and yearly basis (e.g., Binkley et al 1982, Bormann andGordon 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The nitrogen status of the soil may influence fixation as was recognized by Chapman et al 9 when they stated that from an agricultural point of view "greatest nitrogen economy will be achieved where available nitrogen is maintained at the lowest possible point consistent with satisfactory crop performances". In the present experiment nitrogen fixation in the grass--soil systems occurred when the initial soil nitrogen levels were low (0.05 per cent) but not when they were somewhat higher (0.07 and 0.09 per cent).…”
Section: Discussionmentioning
confidence: 99%
“…The use of lysimeters eliminates most of the errors possible in conventional Iield experiments on nitrogen economy and gains of nitrogen have still been found under these circumstances, e.g. C h a p m a n et al 9 reported gains of 40 pounds of nitrogen per acre per year under mustard, S m i t h 25 22 pounds per acre per year under wheat, and G e l ' t s e r 11 from 45 to 66 kg per hectare per year under perennial grasses and irises. In addition there would appear to be some doubt as to the validity of using "efficiency" values determined in pure culture in the laboratory to calculate the possible magnitude of non-symbiotic nitrogen fixation in a medium as complex as soil, particularly since theoretical thermodynamic considerations indicate that the reduction of nitrogen gas to ammonia by glucose would be an exothermic reaction 2.…”
Section: Introductionmentioning
confidence: 99%